Rare immune-related adverse events in patients with melanoma: incidence, spectrum, and clinical presentations. (31st December 2023) - Park, Benjamin C.; Narayanan, Sathya; Gavralidis, Alexander; Ye, Fei; Fan, Run; Sullivan, Ryan J.; Boland, Genevieve; Reynolds, Kerry L; Balko, Justin M.; Carlino, Matteo S.; Long, Georgina V.; Zubiri, Leyre; et al.
ABSTRACT: Immune-related adverse events (irAEs) are side effects of immune checkpoint inhibitor therapy (ICI). While common irAEs have been well characterized, there are more limited data on rare immune related adverse events (RirAEs) due to low incidence. Lack of characterization of these entities has led to difficulties in accurate diagnosis and management. Here, we conducted a multi-institution analysis of all patients with stage III/IV melanoma who developed RirAEs after being treated with ICIs (anti-PD-1/L1, anti-CTLA-4, and combination PD-1/CTLA-4 blockade) at three institutions (Vanderbilt University Medical Center, Massachusetts General Hospital, and Melanoma Institute of Australia). RirAEs were defined as those occurring in approximately <1% of patients treated with anti-PD-1 or <2% with combination. Of 2834 patients who received ICIs, 82 developed RirAEs and were more common with combination PD-1/CTLA-4 blockade (4.6%) vs. anti-PD-1/L1 agents (2.8%). Overall median time from ICI start to RirAE was 86 days (interquartile range 42–235 days) with significantly earlier onset in combination therapy ( p < 0.001). The spectrum of RirAEs spanned across several organ systems. Most RirAEs were grade 2 (57 [41.3%]) and grade 3 (40 [29.0%]) with relatively few grade 4 (11 [8.0%]) or 5 (5 [3.6%]) events. Steroid re-escalation (21.4%) or additional immunosuppression (13.8%) were commonly required. RirAE recurrence occurred in 22.6% with ICI rechallenge; 37.1% had new irAEs with rechallenge. In conclusion, RirAEs associated with ICIs in melanoma patients occurred, in aggregate, in 2–5% of patients treated with anti-PD-1-based therapy. Steroid re-escalation and alternative immunosuppression use were frequently required but fatal irAEs were fairly uncommon.